The integration of exergy criterion in energy planning analysis for 100% renewable system. (1st May 2019) - Bonati, A.; De Luca, G.; Fabozzi, S.; Massarotti, N.; Vanoli, L.
Abstract: This paper presents a new methodology that allows to define a 100% renewable smart energy system in a sustainable manner. The authors integrate the EnergyPlan with a mathematical model that analyzes the energy system from an exergetic point of view taking into account the exergy of the whole energy system and its components. Once multiple scenarios are obtained by EnergyPLAN, the exergetic model identifies the scenario characterized by the highest exergetic efficiency and the lowest energy wasting. This approach is a novelty since the "exergetic" optimization criterion coupled with EnergyPLAN software has never been utilized. Since the best energy system could not be economically attractive, this methodology might support Municipalities in setting up focused incentives to make the sustainable solutions the most cost effective too. The authors present a case study by applying the new methodology to the city of Pompeii. The results show that the best solution provides 21.0 MWe capacity of PV plant, integrated to 8.10 MWe of CHP plant. Due to a high value of critical excess electricity production, 10 MWe heat pumps must be installed. Finally, a solar thermal plant is installed. The proposed system could be only realized if new incentives are provided. Highlights: A 100% renewable energy system is carried out through a new methodology. Energy, exergetic and economic analyses of the case study proposed are presented. A tool to define types of RES plants must be incentive to convert territory in 100% renewable energy.